(untitled) (Anuário Antropológico, 2021)
This essay is one of a series on the arts and forms of emergent common sense in the globally interconnected, politically-semiotically-media fraught, Anthropocenic twenty-first century. The arts restlessly play hopscotch with temporalities and locations. Since the days of Third Cinema, auteur cinema, and national cinemas, films have attempted complex strategies, often mobilizing local and international genre film forms subversively against themselves to create a cinema of laughter, self-recognition, and critique. The 2019 Cannes Jury Award-winning film Bacurau provides an addictively detailed, yet globally accessible, intervention into the struggles over Covid-19, authoritarianism, and erosion of indigenous, black, and other marginalized citizens’ rights. As such, it is a kind of social drama that encompasses expanding breaches in the social fabric beyond its text and reworking temporal relations between pasts and futures.